Retinal detachments secondary to inferior retinal breaks: anatomic outcomes following the use of different surgical techniques - Martin Zinkernagel; Enrico Bernardi; Rodrigo Anguita; Lorenzo Ferro Desideri; Dmitri Artemiev (BMJ Open Ophthalmology)
Purpose To compare the anatomical and functional outcomes of pars plana vitrectomy (PPV) alone versus PPV with the addition of a scleral buckle in treating inferior rhegmatogenous retinal detachments (RRDs).Methods Comparative, retrospective cohort study including patients who were diagnosed with primary inferior RRD, defined as RRD with one or more retinal tears located between 4 and 8 hours, and divided into two treatment groups. Group 1 patients were treated with PPV and gas tamponade alone, whereas group 2 patients were treated with PPV, gas tamponade and the addition of an encirclement band. Demographic and clinical features were collected, and surgical outcomes of both groups were analysed. A univariable logistic regression model evaluated the factors influencing surgical success.Results A total of 161 eyes were included in the study. The average age at diagnosis was 64.1 years. There was a male predominance (66.5%), and most patients had macula-off detachments (54%). Group 1 included 75 eyes (43.1%), whereas group 2 included 86 eyes (56.9%). Baseline best-corrected visual acuity was 1.00 logMAR, improving to 0.62 logMAR at the last visit (p=0.003). No significant difference in primary success rate was observed between the two groups (86.0% with encirclement band vs 80.0% without; p=0.3). The mean follow-up period was 29 weeks (SD 39).Conclusions PPV alone may be as effective as PPV with an encirclement band when treating inferior RRDs. The choice of tamponade does not appear to significantly influence anatomical success, and short-acting gas can be considered sufficient for favourable outcomes.